The Influence of Mind Mapping Technique and Studentsâ Attitude toward Studentsâ Ability in Writing a Recount Text of the Eighth Grade Students of State Junior High School 45 Palembang - Firmansyah, Arie (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstractThe Research is title The Influence of mind mapping technique and studentsâ attitude toward the studentsâ ability in writing a recount text the First year students of SMPN 45 Palembang. The findings of the study showed that: (1) there was a significant difference in average score of writing a recount text between the positive and negative studentsâ attitude who were taught using mind mapping technique, indicated by p-output (0.002).(2) there was a significant difference in average score of writing a recount text between the positive and negative studentsâ attitude who were taught using conventional strategy, indicated by p-output (0.003). (3) there was a significant difference in average score of writing a recount text between the positive studentsâ attitude who were taught using mind mapping technique and those who were taught using conventional strategy, indicated by p-output (0.000). Therefore, it can be concluded that Mind Mapping Technique improved studentsâ writing achievement.Â Keywords: Mind Mapping Technique, Studentsâ Attitude, Studentsâ Ability